Pengembangan Keterampilan Teknis Pelajar SMK di Palembang Melalui Pelatihan Dasar Pembuatan Aplikasi: Development of Technical Skills for Vocational High School Students in Palembang Through Basic Application Development Training - Bambang Wijaya Putra; Dwi Candra Yuniar; Minulya Eska Nugraha; Herlina Febiyanti; Rizky Nova Dona (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
This study focuses on the development of technical skills among vocational high school students in Palembang through basic application development training. The training, conducted on May 29, 2024, at SMK Muhammadiyah 1 Palembang, involved 20 students from grades X, XI, and XII. The training aimed to provide foundational knowledge in creating simple applications using software like XAMPP and WordPress, essential tools for web application development. The program included theoretical instruction, practical application, pre-test and post-test evaluations, and hands-on coding sessions. The pre-test results indicated a moderate understanding of the subject, with an average score of 64.45. Post-training assessments showed significant improvement, with an average post-test score of 90. The N-gain score analysis revealed that 65% of the participants demonstrated a high level of improvement, while 35% showed moderate improvement. The training successfully enhanced the students' technical skills in programming and application development, equipping them with the knowledge to create simple cashier applications, crucial for small and medium enterprises. This hands-on approach to learning fostered creativity and innovation, providing students with practical skills to meet the demands of the modern workforce. This initiative not only fulfilled the educational objectives of SMK but also aligned with the broader goal of community service by higher education institutions, showcasing a successful model of vocational training in application development